Precision materials: Computational design methods of accurate protein materials. (June 2022) - Wang, Shunzhi; Ben-Sasson, Ariel J.
Abstract: Nature has evolved a vast repertoire of structures and functions based on an ordered, orchestrated, protein building-blocks assembly. For decades these sophisticated materials have been studied, mimicked, and repurposed, yet recently, computational protein engineering methods provided an alternative route: creating protein materials de-novo, surpassing evolutionary constraints and optimized for specific tasks. We highlight two areas of research that fundamentally accelerate design of structurally well-defined programmable protein materials. First, implementations of hierarchical assembly and geometric sampling (docking) strategies to create designable backbones under pre-specified symmetry constraints. Second, progress in protein–protein interfaces and sequence design methods, using Rosetta, that drive programmable supramolecular assemblies. These approaches have proven effective in generating diverse protein assemblies in 0-, 1-, 2-, and 3-dimensional architectures (constituting single or multiple components), and as part of a synthetic or a biological system. We expect these methods shall transform the toolbox of protein designers developing next generation synthetic and biological materials.